A Mild, Efficient and Sustainable Tetrahydropyranylation of Alcohols Promoted by Acidic Natural Deep Eutectic Solvents. Issue 3 (2nd January 2023) - Arnodo, Davide; De Nardo, Eugenio; Ghinato, Simone; Baldino, Salvatore; Blangetti, Marco; Prandi, Cristina
Abstract: A straightforward protocol to promote the tetrahydropyranylation of alcohols, using for the first time bioinspired acidic natural deep eutectic solvents (NADESs) as non‐innocent reaction media under mild reaction conditions, was reported. This approach enables the preparation of several tetrahydropyranyl (THP) ethers starting from primary, secondary and tertiary alcohols in short reaction times and with high levels of chemoselectivity, working under air and without the need of additional catalyst. The sustainability of the methodology was further highlighted by its scalability and the easy recyclability of the NADES, allowing multigram preparations of THP ethers without any loss of the catalytic activity of the reaction media up to ten recycling steps. Telescoped, one‐pot tetrahydropyranylation/nucleophilic acyl substitution transformations using the same eutectic mixture were also demonstrated. Abstract : A simple, scalable, and sustainable access to tetrahydropyranyl (THP) ethers from alcohols was achieved exploiting the dual role of acidic natural deep eutectic solvents (NADESs) both as catalysts and reaction media, working under bench‐type and mild reaction conditions. The easy scalability of the process and the recyclability of the NADES add great value in terms of efficiency and environmentally sustainability.